Arendelle puff / Khairul Hadi Hashim ... [et al.] - Hashim, Khairul Hadi; Ramlan, Mohamad Ikmal; Kamal Shahrizan, Izzat Syahmi; Nor Azman, Nor Natasya; Azmi, Nur Liyana (2016)
ARENDELLE PUFF ENTERPRISE is a company focuses on food production in Malaysia. Puff was very well known back then but now its popularity is kind of fading away from its own domain, which is our country. So the idea of getting this puff back on the top of the list of our very well-known foods came after Catherine Chin Wan Ping Coombes had won the MasterChef UK 2014 with our local food. We have three fillings as the option for our customers to choose which are meatball as the main filling, chicken and otak-otak. The bigger shape of our puffs and the combination of the westerns would make it as our signature. The company is not only providing frozen puff, we also cook our puff to be serving to the customer. The company is concentrating on customers satisfactions. We will provide our customers with all the needs they need. We also attract customers from the youngest age to the oldest age. We will expect that our business will developed in the near future because our puff is an extraordinary